Seven Unpublished Letters by Mikhail I. Rostovtzeff to Vittorio Macchioro (1910-1913) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2021)
Rostovtzeff and Macchioro, very different scholars both on human and scientific level, never cultivated a friendly collaboration, except in the years 1910-13, as attested by the (so far only known) seven letters sent by the Russian scholar to Macchioro and now preserved in the “Fondo Macchioro” of the University of Trieste. In two letters of 1910 Rostovtzeff asked Macchioro for photographs of Pompeian wall paintings, while in five letters of 1912-1913 he agreed to contribute with a short article for the new journal “Neapolis”, directed by Macchioro. In this work Rostovtzeff summarized his own historical-artistic interpretation of the Canusian “Lagrasta Hypogea”, that had recently attracted also Macchioro’s interest. At the end of the 1930s, Macchioro was contacted by Vito Lagrasta, a senior official of the PNF General Secretariat, who aspired to compose a monograph on the Canusian Hypogea.
Keywords: Rostovtzeff; Macchioro; pompeian wall painting; tombs of Southern Russia; “Oriental” Hellenistic koiné; Lagrasta hypogea; Vito Lagrasta